The unrealized state attempt of establishing German autonomy in Kazakhstan (1950–1970s) - Isakhan, G.T.; Khassenova, Zh.O.; Mazhitova, Zh.S.; Bogenbayeva, A.K. (Karaganda University named after academician E.A.Buketov, 2023)
The article considers important historical aspects of the national movement of the Soviet Germans in Kazakhstan in the second half of the 20th century. The study highlights the contribution, forced resettlement, labor, numbers, the discriminatory policy of the authorities as well as the emergence of the emigrant and autonomist moods of the Germans in Kazakhstan. The reasons for the emergence of the “German question” were revealed and characterized. The struggle of the Germans for restoration of the autonomy on the Volga and the campaigns of German delegations to the Kremlin with the aim to resolve this issue are noted. The antiautonomist movement of youth and students in Tselinograd oblast in June 1979 is evaluated. The authors express their opinion on the causes and consequences for Kazakhstani society of the failed attempt to establish German autonomy.
Қазақстанда неміс автономиясын құрудың мемлекеттік іске асырылмаған әрекеті (1950–1970 жж.)
Нереализованная государственная попытка создания немецкой автономии в Казахстане (1950–1970-е гг.)
Keywords: German population; deportation; Soviet Union; Soviet Germans; emigration moods; national movement; Volga region; Tselinograd event